(untitled) (Praxis Educativa, 2018)
Through ecclesiastical reports, interviews with teachers, surveyors and peasants, cartography, surveys and other complementary sources, we seek to reconstruct the trajectory of educational practice, recreate the institutional history of the school and recover the meaning of access to it Rural Chos Malal, central Argentina. We use the category "edge space" to refer to those places less embedded in the dynamics of capital, with dependence and domination of other spaces, but which have a margin of autonomy in their territorial and practical logics. To educate in the border supposes to face diverse obstacles to be able to accede and to remain in the school. In this way we advance in the process of territorialization of this rural place situating it spatially and temporally, and then raise four significant moments in the educational practice of the place.